The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c6nr03360a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reactions at the graphitic step-edge: changes in product distribution of catalytic reactions as a tool to explore the environment within carbon nanoreactors

Abstract: A series of explorative cross-coupling reactions have been developed to investigate the local nanoscale environment around catalytically active Pd(II)complexes encapsulated within hollow graphitised nanofiber (GNF). Two new fullerene-containing and fullerene-free Pd(II)Salen catalysts have been synthesised, and their activity and selectivity towards different substrates has been explored in nanoreactors. The catalysts not only show a significant increase in activity and stability upon heterogenisation at the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
(33 reference statements)
1
11
0
Order By: Relevance
“…These results are in agreement with previous observations that performing reactions in confinement has a number of important effects on catalysis and alters the outcome of reactions in a complex fashion; 15 by enhancing the activity of nanaoparticle cataltysts, 47 increasing the local concentration of reagents and thus increasing the rate of reactions, 48 and by imposing restritions on both the transition states of intermediates 41 and the flow of reactants in and products out of the nanoreactor. 27 To investigate the 3D structure of the materials the experimentally measured active surface area of RuNPs@SWNT, RuNPs@GNF and commercial Ru/C catalysts were compared with theoretically calculated surface areas based on ideal models of the materials, i.e.…”
supporting
confidence: 93%
“…These results are in agreement with previous observations that performing reactions in confinement has a number of important effects on catalysis and alters the outcome of reactions in a complex fashion; 15 by enhancing the activity of nanaoparticle cataltysts, 47 increasing the local concentration of reagents and thus increasing the rate of reactions, 48 and by imposing restritions on both the transition states of intermediates 41 and the flow of reactants in and products out of the nanoreactor. 27 To investigate the 3D structure of the materials the experimentally measured active surface area of RuNPs@SWNT, RuNPs@GNF and commercial Ru/C catalysts were compared with theoretically calculated surface areas based on ideal models of the materials, i.e.…”
supporting
confidence: 93%
“…Carbon nanotubes are mechanically robust, thermally and chemically stable cylinders of sp 2 ‐carbon that can be used to immobilize both molecules and nanoparticles which efficiently adsorb onto the nanotube walls and/or are encapsulated within the internal cavity of the nanotube via noncovalent interactions such as van der Waals forces . Once the catalyst is immobilized in the hollow structure, catalytic chemical reactions which occur within the accessible nanoscale space of the nanoreactor interior can benefit from enhanced rates of reactions and selectivity …”
Section: Introductionmentioning
confidence: 99%
“…PtNPs confined within GNF were also investigated in the oxygen reduction reaction (ORR) by Gimenez‐Lopez et al and outstanding electrochemical stability was observed over 50 000 cycles of ORR, with the PtNPs stabilized by the step edges significantly more strongly than commercial PtNPs on carbon black . In addition to NP based catalysts, Lebedeva et al synthesized fullerene containing and fullerene free Pd(II)Salen metal complexes and encapsulated both species on the step edges of the internal GNF surface to form catalysts which displayed significantly higher activity and selectivity in several Heck reactions compared to the reactions in solution …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations